Highly selective diversion with proactive leakage management after low anterior resection for rectal cancer. Issue 6 (1st February 2021) - Talboom, K; Vogel, I; Blok, R D; Roodbeen, S X; Ponsioen, C Y; Bemelman, W A; Hompes, R; Tanis, P J
Abstract : In this single center case series with nine percent primary diversion, 86 of 94 patients alive and with complete follow-up at one year had a functioning anastomosis. Seventy-five of the initial 99 patients never had a stoma. Meaning: Highly selective fecal diversion in combination with proactive leakage management, low anastomoses can be preserved safely, and the majority of patients will be spared all disadvantages of a diverting stoma.